1995
DOI: 10.1530/jrf.0.1050099
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hamster zona-free oocytes by homologous and heterologous spermatozoa

Abstract: Spermatozoa of a wide variety of species can fuse with zona-free hamster oocytes. Zona

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 1 publication
3
25
0
1
Order By: Relevance
“…Immediately following sperm attachment, oocytes were continuously monitored. Ca 2ϩ oscillations of oocytes induced by epididymal spermatozoa in golden hamster have been described elsewhere (Swann, 1990;Miyazaki et al, 1992;Maleszewski et al, 1997). In the present study, epididymal spermatozoa induced Ca 2ϩ oscillations in 65.4% (17 of 26) of the oocytes (Table II).…”
Section: Ca 2⍣ Oscillations Induced By Epididymal or Ejaculated Spermsupporting
confidence: 73%
“…Immediately following sperm attachment, oocytes were continuously monitored. Ca 2ϩ oscillations of oocytes induced by epididymal spermatozoa in golden hamster have been described elsewhere (Swann, 1990;Miyazaki et al, 1992;Maleszewski et al, 1997). In the present study, epididymal spermatozoa induced Ca 2ϩ oscillations in 65.4% (17 of 26) of the oocytes (Table II).…”
Section: Ca 2⍣ Oscillations Induced By Epididymal or Ejaculated Spermsupporting
confidence: 73%
“…Our results coincide with the finding of Malezewenski et al [23], who reported on the activation of oocytes after sperm penetration. Their study was conducted with homologous and heterologous spermatozoa and zona pellucida-free hamster oocytes.…”
Section: Discussionsupporting
confidence: 93%
“…It is now well established that the pronucleus formation and second polar body extrusion in fertilized eggs and parthenogenetically activated oocytes can be induced via the inactivation of MPF [10,11,[22][23][24]. Recently, the inactivation of MAP kinase induced long after inactivation of MPF, has been shown to be required for pronucleus formation and second polar body extrusion [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, olive oil generated the greatest number of sperm per oocyte as well as the higher rate of penetration. Penetration testing conducted by co-incubation of gametes is more predictive of fertility compared to tests that evaluate the sperm alone 41,42 , in addition to this test have shown sensitivity in detecting fertilizing ability of boar sperm 29 .…”
Section: Discussionmentioning
confidence: 99%
“…After co-incubation, oocytes were recovered, washed, stained with Hoechst 33342 (10 mg / ml) and evaluated in epifluorescence microscope at 400x. Finally, oocytes were considered penetrated when their zona pellucida contained at least one sperm in perivitelline or cytoplasm space 29,30 .…”
Section: Methodsmentioning
confidence: 99%